Evaluating the effect of dopamine-geldanamycin hybrids on anticancer activity - Thongchai Taechowisan, Tipparat Samsawat, Chanjira Jaramornburapong, Weerachai Phutdhawong, Waya S. Phutdhawong (Journal of Applied Pharmaceutical Science, 2021)
Geldanamycin (GDM) is an antibiotic isolated from Streptomyces zerumbet W14 that specifically targets and deactivates heat shock protein 90 (Hsp90), directed to the functional protein deficiency. The utilization management of GDM has been limited by its poor water solubility and hepatotoxicity. Five new dopamine-geldanamycin hybrids (DGH), compounds 2 to 6, were synthesized from GDM (1). Solubility, cytotoxicity, anticancer activity, molecular docking, and ADMET analyses were carried out. The solubility of DGH in water was 0.386–5.464 mM, higher than that of compound 1. These compounds showed weak cytotoxic activity against Vero cells and LLC-MK2, with IC50 values in the range of 104.52–496.31 µg/ml. Compounds 2, 3, and 6 were also active against MDA-MB231 cells with IC50 values of 41.88, 52.12, and 70.93 µg/ml, respectively. They interacted positively with Hsp90, showing binding free energy (âˆ†G) of −97.03 to −101.06 kcal/mol, which indicated lower Hsp90 affinity compared with that of GDM (−133.06 kcal/mol) and 17-dimethylamino ethylamino-17-demethoxygeldanamycin (−136.55 kcal/mol), despite being partly bound in the active site (compounds 2, 3, and 6) or outside the active site (compound 4). Since compound 4 bound outside the active side and compound 5 did not bind to any part of Hsp90, they were not active on cytotoxicity against both normal cells and cancer cells. The predicted results showed that the ADMET parameters of DGH were similar to those of GDM. Furthermore, the experimental results are associated with a theoretical basis by molecular docking and ADMET analysis. The study findings revealed, through molecular docking and ADMET analysis, that the development of DGH improved the pharmacokinetic profiles of solubility, cytotoxicity, and anticancer activities. We, therefore, recommend DGH as a potential alternative treatment agent for some cancers.
Keywords: ADMET analysis, anticancer activity, cytotoxicity activity, dopamine-geldanamycin hybrids, heat shock protein 90, molecular docking, water solubility.